1997
DOI: 10.1093/intimm/9.11.1669
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of CD8+ T cells from subunit-vaccinated and infected H-2b mice recognizing the 38 kDa antigen of Mycobacterium tuberculosis

Abstract: CD8+ T cells have been implicated in protective anti-tuberculous immune responses, but little is known about the identity of mycobacterial antigens recognized by CD8+ T cells. In this study we identified the Mycobacterium tuberculosis 38 kDa protein as a target for murine CD8+ cytotoxic T lymphocytes (CTL) which were induced by vaccination of C57BL/6 mice with DNA delivered with a plasmid, with transfected tumour cells or by infection with tubercle bacilli. Using overlapping synthetic peptides covering the who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Apart from the ability to make cytokines, CD8 ϩ T cells may also function as CTLs; the development of CD8 ϩ CTLs during acute murine tuberculosis has been documented (17,24,33,35,36,39). We demonstrated that, 3 weeks postchallenge, the lungs of memory mice contained CD8…”
Section: Cytotoxic Function Of Memory Cd8 ؉ T Cells Previously We Dmentioning
confidence: 75%
See 1 more Smart Citation
“…Apart from the ability to make cytokines, CD8 ϩ T cells may also function as CTLs; the development of CD8 ϩ CTLs during acute murine tuberculosis has been documented (17,24,33,35,36,39). We demonstrated that, 3 weeks postchallenge, the lungs of memory mice contained CD8…”
Section: Cytotoxic Function Of Memory Cd8 ؉ T Cells Previously We Dmentioning
confidence: 75%
“…5). Although several antigens have been shown to be recognized by mycobacterium-specific CD8 ϩ T cells (14,28,35,39), the antigenic repertoire recognized by CD8 ϩ T cells in tuberculosis remains largely uncharacterized. Therefore, we have used infected macrophages as targets for specific CD8 ϩ CTLs to ensure that complete spectrum of antigens is presented to T cells during the assay.…”
Section: Cytotoxic Function Of Memory Cd8 ؉ T Cells Previously We Dmentioning
confidence: 99%
“…ϩ T cells specific for epitopes of the 38-kDa glycolipoprotein were isolated (20,36). However, with the exception of hsp65-specific CTLs generated by immunization with a cell line expressing this Ag (19), no other reports document the ability of CD8 ϩ CTLs to lyse M infected with live M. tuberculosis, which is an important component of protection by CTLs.…”
Section: Discussionmentioning
confidence: 99%
“…Second, DNA vaccines may contribute to the improved protection against M. tuberculosis infection by priming both CD4 ϩ and CD8 ϩ T cells. DNA immunization can stimulate both T-cell subsets (19) and is more potent than mycobacteria at priming naive CD8 ϩ T cells (3,20). Third, BCG immunization may effectively amplify mycobacterium-specific CD8 ϩ T-cell responses primed by DNA immunization, as the requirements for activation of effector/ memory T cells are less stringent than those for their naive counterparts (18).…”
Section: Vol 69 2001mentioning
confidence: 99%